2008
DOI: 10.1026/0942-5403.17.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung des Schlafverhaltens im Säuglingsalter

Abstract: In der vorliegenden Arbeit werden Beziehungen zwischen dem Geburtsgewicht, der kindlichen Gewichtsentwicklung, der positiven und negativen Reaktivität des Kindes und der mütterlichen Depressionsneigung/Ängstlichkeit mit der Entwicklung von Schlafverhaltensmerkmalen am Ende des ersten Lebensjahres untersucht. An der Längsschnittstudie nahmen insgesamt 101 Bezugspersonen-Kind-Paare teil. Alle Kinder waren gesunde Erstgeborene mit einem Geburtsgewicht über 2500 g. Untersuchungen fanden im Alter der Kinder von vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Martini et al (2017) described fussy/difficult infant temperament as an important factor associated with extensive infant crying, eating, and sleeping problems. In several other studies, infant negative temperament was identified as a predictor of sleep disturbance, with impeded self-soothing, an inability to adapt, diminished smiling, and reduced activity used as markers of infant negative temperament (Hirtz et al, 1993;Touchette et al, 2005;Heitkamp and Pauli-Pott, 2008;Weinraub et al, 2012;Sorondo and Reeb-Sutherland, 2015). Also, perceived infant negative emotionality in our study was associated with more sleeping and crying problems as well as more eating problems.…”
Section: Regulatory Problems and Other Infant And Maternal Characteristicssupporting
confidence: 67%
“…Martini et al (2017) described fussy/difficult infant temperament as an important factor associated with extensive infant crying, eating, and sleeping problems. In several other studies, infant negative temperament was identified as a predictor of sleep disturbance, with impeded self-soothing, an inability to adapt, diminished smiling, and reduced activity used as markers of infant negative temperament (Hirtz et al, 1993;Touchette et al, 2005;Heitkamp and Pauli-Pott, 2008;Weinraub et al, 2012;Sorondo and Reeb-Sutherland, 2015). Also, perceived infant negative emotionality in our study was associated with more sleeping and crying problems as well as more eating problems.…”
Section: Regulatory Problems and Other Infant And Maternal Characteristicssupporting
confidence: 67%